THE INFLUENCE OF STRATEGIC ORIENTATION, ORGANIZATIONAL CAPABILITY AND GOVERNMENT SUPPORT ON THE SUSTAINABLE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Abiyoga, Adis; Suprapti, Ni Wayan Sri; Setiawan, Putu Yudi; Suparna, Gede (Distribusi - Journal of Management and Business, 2025)
The study aims to explore the influence of strategic orientation on sustainable performance of organic farming in the Bali Province. The data used in the study covers the strategic issues of agriculture in Bali, the importance of the agricultural sector for the economic and cultural life of Bali, as well as the role of the Government of the Province of Bali in making the sector a major focus of development. There is still very limited research using systematic literature reviews, especially in the context of the agricultural sector. The research uses the method of Systematic Literature Review (SLR) by looking for relevance from various previous research articles. The results show that strategic orientations, such as market orientation and technology orientation, have an important influence on the sustainable performance of organic farming. In addition, innovation and marketing capabilities also play a role in improving the sustainable performance of organic farming. Government support has proven to be a key factor in boosting the success and growth of the organic farming sector in Bali.